2020
DOI: 10.1186/s12967-020-02397-7
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity measures in patients with myalgic encephalomyelitis/chronic fatigue syndrome: correlations between peak oxygen consumption, the physical functioning scale of the SF-36 questionnaire, and the number of steps from an activity meter

Abstract: Background: Most studies to assess effort intolerance in patients with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) have used questionnaires. Few studies have compared questionnaires with objective measures like an actometer or an exercise test. This study compared three measures of physical activity in ME/CFS patients: the physical functioning scale (PFS) of the SF-36, the number of steps/day (Steps) using an actometer, and the %peak VO 2 of a cardiopulmonary stress test. Methods: Female ME/CFS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 55 publications
3
11
0
Order By: Relevance
“…For SF-36 PF and steps per day, this distinction between severity groups is similar to what we have seen in our previous studies [ 7 , 8 ], and also to the present study. The correlation between SF-36 PF and steps was significant, in agreement with a previous study [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For SF-36 PF and steps per day, this distinction between severity groups is similar to what we have seen in our previous studies [ 7 , 8 ], and also to the present study. The correlation between SF-36 PF and steps was significant, in agreement with a previous study [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…Several studies for evaluation of accuracy have been performed [16]. Both our group and others have used steps per 24 hours as an objective outcome measure in studies with ME/CFS, using different activity tracker technologies [5][6][7][8][17][18][19]. The overall impression is that the measurement of steps in particular seems to have acceptable accuracy in controlled studies, and may be a useful readout in a clinical setting [16,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic skeletal muscle abnormalities are present ME/CFS [6,41,42], and pain in those with co-morbid fibromyalgia can also limit maximal exercise performance. In support of including those with maximal clinical effort but an RER less than 1.1, we have recently shown that adults with ME/CFS with and without an RER of at least 1.1 did not differ with regard to correlations between other measures of exercise, including the physical activity subscale of the SF-36, peak oxygen consumption and the number of steps per day [43]. In those with a concomitant diagnosis of fibromyalgia the RER in that study was significantly lower than in the ME/CFS patients without fibromyalgia; exercise in this subgroup was terminated due to of muscle pain.…”
Section: Two-day Cardiopulmonary Exercise Test Studies Reported In LImentioning
confidence: 73%
“…The reasons for the low diagnostic capacity of the ventilatory threshold are unknown and need to be explored in future studies. In a previous study, we showed highly significant correlations between the physical functioning scale, the number of steps/day and the percent peak oxygen consumption in female ME/CFS patients [ 23 ]. Despite the highly significant correlations, a large variation between the three measures was found in that study.…”
Section: Discussionmentioning
confidence: 99%
“…In 99 female patients, we correlated the physical activity subscale of the SF-36 with more objective measures as the number of steps per day on an activity tracker and the percent predicted peak oxygen consumption. Subgroup analysis of a RER over or under 1.1, the presence or absence of fibromyalgia, the use or non-use of pain-medication and a subdivision above and below a BMI of 30 had no impact on the correlations [ 23 ].…”
Section: Discussionmentioning
confidence: 99%